The Release of 24 h Infravesical Obstruction in Mice: Changes in Molecular, Morphological, and Functional Parameters for 14-Day Observation - Lu, Yutao; Manson, Scott R.; de Araujo, Isabela Bastos Binotti Abreu; Austin, Paul F.; Djurhuus, Jens C.; Olsen, L. Henning; Nørregaard, Rikke (Frontiers in Medicine, 2022)
Bladder outlet obstruction (BOO) induces bladder dysfunction and altered bladder architecture. Irrespective of the release of the obstruction, persistent bladder dysfunction severely affects the quality of life. A better understanding of the repair process offers an opportunity to enhance postintervention management. We subsequently evaluated the postobstructive repair process in mice subjected to 24 h BOO followed by release. Male and female mice bladders were obstructed for 24 h by placing a clip around the bladder neck. After the release of obstruction, the mice were studied for 3, 7, and 14 days to observe the bladder repair process over time. Voiding frequency and volume were recorded using the voiding spot assay, and the transcutaneous glomerular filtration rate (tGFR) was measured. Fibrogenesis and associated gene expressions and altered protein levels were evaluated in the bladder using histology, quantatative polymerase chain reaction (qPCR), and Western blot analyses. Bladder wall thickness was increased in both genders over time but occurred later in female mice. Moreover, collagen deposition in the smooth muscle layer increased over time in both genders. Male mice showed a decreased average voided volume at 3 days post release, while female mice showed no significant change during the time course. Fibrosis-related molecular events, including upregulation of fibronectin (FN) protein and Collagen-3 (Col-3) mRNA expression, were transient and normalized again at 14 days in both genders. Transforming growth factor-β (TGF-β) and bone morphogenic protein (BMP)-7 mRNA expressions were upregulated at 14 days post release in both genders. Transcutaneous GFR remained normal during the time course. Release of 24 h BOO initiated a bladder remodeling process. The animal model enables a wide range of experiments to study bladder remodeling, and gender differences offer potential targets for understanding bladder fibrosis and adaptation with BOO.